Short-Time Work Extensions - Christina Brinkmann; Simon Jäger; Moritz Kuhn; Farzad Saidi; Stefanie Wolter (Institute of Labor Economics (IZA), 2024)
Governments use short-time work (STW) schemes to subsidize job preservation during crises. We study the take-up of STW and its effects on worker outcomes and firm behavior using German administrative data from 2009 to 2021. Establishments utilizing STW tend to have higher wages, be larger, and have falling employment even before STW take-up. More adverse selection occurred during the COVID-19 pandemic. Within firms, STW is targeted towards workers likely to stay even in the absence of STW. To study the effects of STW, we examine two dimensions of policy variation: STW eligibility and extensions of potential benefit duration (PBD). Workers above retirement age, ineligible for STW, have identical employment trajectories compared to their slightly younger, eligible peers when their establishment takes up STW. A 2012 reform doubling PBD from 6 to 12 months did not secure employment at treated firms 12 months after take-up, with minimal heterogeneity across worker characteristics. However, treated and control firms experienced substantial and persistent differences in their wage trajectories, with control firms without extensions lowering wages compared to treated firms. Across cells, larger wage effects corresponded with smaller employment effects, consistent with downward wage flexibility preventing layoffs and substituting for the employment protection effects of STW. Our research designs reveal that STW extensions in Germany did not significantly improve short- or long-term employment outcomes.
Keywords: J01; J08; J30; J41; 330; stabilization policies; short-time work; wage rigidity; labor market institutions; intra-firm insurance